The Influence of Green Brand Authenticity on Consumer Purchase Intention: Mediating Role of Environmental Commitment - Ghia Subagja; Bella Hartati; Evrina Evrina (Lembaga Pengembangan Kinerja Dosen, 2025)
The rising demand for credible sustainability practices has positioned green brand authenticity as a critical factor influencing consumer evaluation and behavior. However, existing studies show inconsistent results regarding the direct impact of authenticity on purchase intention and provide limited insight into the psychological mechanisms underlying this relationship. This research addresses these gaps by investigating the influence of green brand authenticity on consumer purchase intention and examining the mediating role of environmental commitment. A quantitative survey was conducted with 150 respondents who had experience purchasing environmentally friendly products. Data were analyzed using multiple regression and mediation testing through a three-equation model supported by Sobel analysis. The results show that green brand authenticity significantly and positively influences both environmental commitment and consumer purchase intention. Furthermore, environmental commitment was found to partially mediate the rela-tionship, indicating that authenticity not only enhances consumers’ cognitive trust in a brand’s envi-ronmental claims but also strengthens their moral engagement with ecological values, which in turn in-creases their likelihood of purchasing green products. These findings contribute to sustainability research by demonstrating the importance of internal psychological factors in shaping consumer responses to authentic environmental initiatives. The study concludes that authentic green branding strategies can foster deeper environmental commitment and more consistent purchasing behavior. Limitations include the cross-sectional design and the use of purposive sampling, suggesting that future research should consider longitudinal and cross-cultural approaches to validate the robustness of these findings.